Conceptual development of revenue and yield management system for shipping business - Lie, Zhi Jian. (2009)
Yield management system is being used readily in the airlines industry but it still remains as a relatively new concept in the shipping market. This report discuss on the feasibility of the application of this yield management concept into the shipping operations